2003
DOI: 10.1038/nature01712
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin requirement in branching morphogenesis

Abstract: Many organs, including salivary glands, lung and kidney, are formed during embryonic development by epithelial branching. In branching morphogenesis, repetitive epithelial cleft and bud formation create the complex three-dimensional branching structures characteristic of many organs. Although the mechanisms are poorly understood, one might involve the site-specific accumulation of some regulatory protein. Here we show that the extracellular matrix protein fibronectin is essential for cleft formation during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
449
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 499 publications
(470 citation statements)
references
References 26 publications
16
449
0
5
Order By: Relevance
“…We hypothesized that LPS might disrupt similar processes in the fetal lung during distal development. Fibronectin mediates cell adhesion and spreading and is required for branching morphogenesis in the submandibular gland and during development of proximal conducting airways (Sakai et al, 2003). We, therefore, tested if fibronectin was also required for distal lung branching and if LPS could alter its expression.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that LPS might disrupt similar processes in the fetal lung during distal development. Fibronectin mediates cell adhesion and spreading and is required for branching morphogenesis in the submandibular gland and during development of proximal conducting airways (Sakai et al, 2003). We, therefore, tested if fibronectin was also required for distal lung branching and if LPS could alter its expression.…”
Section: Resultsmentioning
confidence: 99%
“…The UF filter used in this study retains proteins larger than 100 kDa, allowing smaller proteins to pass into the filtrate. This is likely to enable cell growth and potentially extracellular matrix production (ECM) by the cells [29,30]. However, it has been reported that the lack of large molecules, such as glycoproteins, may have adverse effects on cell differentiation and proliferation [31].…”
Section: Discussionmentioning
confidence: 99%
“…The ECM protein fibronectin has also been identified as a putative cleft initiator (Sakai et al , 2003). It accumulates in the clefts and appears to direct its own inward translocation deeper into the cleft as cleft progression occurs (Larsen et al , 2006).…”
Section: Mechanical Forces Generated By the Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…Consistent with the possibility that E-cadherin functions in place of other junctional proteins to stabilize external epithelial surfaces, the localization of E-cadherin is considerably stronger between cell junctions of outer bud epithelial cells than those between the inner bud cells (Walker et al, 2008). However, when a cleft forms to interrupt this layer of outer epithelial cells, E-cadherin localization and expression diminish as cell shift from cell-cell to cell-matrix adhesion (Sakai et al, 2003). …”
Section: Cell-cell Interactionsmentioning
confidence: 99%